The Outcasts of 19 Schuyler place - Konigsburg, E.L. (London : Walker Books, 2004)
Upon leaving an oppressive summer camp, twelve-year-old Margaret Rose Kane spearheads a campaign to preserve three unique towers her great-uncles have been building in their backyard for more than forty years.
Keywords: Individuality -- Fiction; Social action -- Fiction; Uncles -- Fiction